GE_GERICHTE P/13615/2014 vom 19. Dezember 2016 - GE Cour de justice (2016)
CONTRAINTE(DROIT PÉNAL); TENTATIVE(DROIT PÉNAL); COMMANDEMENT DE PAYER; POURSUITE POUR DETTES | CP.181; CP.178; CP.173; LP.79; LP.80; LP.82; CC.28; CO.49; CO.60